Cosmc Disruption-Mediated Aberrant O-glycosylation Suppresses Breast Cancer Cell Growth via Impairment of CD44 - Du, Tan (Cancer Manag Res, 2020)
BACKGROUND: Breast cancer remains the most lethal malignancy in women worldwide. Aberrant O-glycosylation is closely related to many human diseases, including breast carcinoma; however, its precise role in cancer development is insufficiently understood. Cosmc is an endoplasmic reticulum-localized chaperone that regulates the O-glycosylation of proteins. Cosmc dysfunction results in inactive T-synthase and expression of truncated O-glycans such as Tn antigen. Here we investigated the impact of Cosmc disruption-mediated aberrant O-glycosylation on breast cancer cell development through in vitro and in vivo experiments. MATERIALS AND METHODS: We deleted the Cosmc gene in two breast cancer cell lines (MCF7, T47D) using the CRISPR/Cas-9 system and then measured the expression levels of Tn antigen. The proliferation of Tn-positive cells was examined by RTCA, colony formation and in vivo experiments. The effects of Cosmc deficiency on glycoprotein CD44 and MAPK pathway were also determined. RESULTS: Both in vitro and in vivo studies showed that Cosmc deficiency markedly suppressed breast cancer cell growth compared with the corresponding controls. Mechanistically, Cosmc disruption impaired the protein expression of CD44 and the associated MAPK signaling pathway; the latter plays a crucial role in cell proliferation. Reconstitution of CD44 substantially reversed the observed alterations, confirming that CD44 requires normal O-glycosylation for its proper expression and activation of the related signaling pathway. CONCLUSION: This study showed that Cosmc deficiency-mediated aberrant O-glycosylation suppressed breast cancer cell growth, which was likely mediated by the impairment of CD44 expression.